Aquisição de comportamentos simbólicos por bebês - Roncato, Graziele de Aguiar (Universidade Federal de São Carlos, 2020)
Behavior Analysis as behavioral study language and classification like behavior processes according to the Stimulus Control area. However, the mode and prerequisites for symbolic responses are not fully established. Hence, the importance of studying babies who are starting to learn the verbal repertoire and have a short history of reinforcement. Thus, this work aim to investigate language acquisition by young children, more specifically, to observe contingencies Response – Consequence, with the management of consequences given to children's vocalizations and to investigate the handling of antecedent stimuli for purchase a verbal / symbolic response. We propose three studies. The first study investigated the effect that imitation and directed speech on the frequency of babies' vocalizations. Ten babies aged up to 13 months participated in the study and the collection took place in six sessions, three with conditions of imitation of the adult to the baby's vocalizations and three with conditions of speech directed from the adult to the baby's vocalizations. As a result, both contingent conditions (imitation and speech) function as reinforcers for babies' vocalizations. The second study investigated, through a systematic review, the procedures and results of the last 30 years of research on the establishment of equivalent stimulus classes in babies up to 36 months. As a result, we found15 articles; in 14, there were reports of emergence of stimulus classes. Finally, the third study investigated the acquisition of equivalent stimulus classes by babies up to 24 months. For this purpose, a procedure was proposed with auditory-visual baseline teaching (AB and AC) and naming, transitivity (BC), equivalence (CB) tests and to verify whether the specific consequence would be part of the class. Three of five participants had performance that indicates emergence of classes; one of them did not name the visual stimuli. Two participants did not show class emergence, even one naming the stimuli. The results suggest that the contingent responses from verbal community, with different responses topographies, acts as a reinforcer to increase the frequency of children's vocal responses, prerequisites for future verbal behaviors; and babies up to 24 months of age are able to emit responses symbolic, even without naming.
Symbolic behavior acquisition by babies
Keywords: Crianças pequenas; Comportamento verbal; Classes de estímulos equivalentes; Young children; Verbal behavior; Stimulus equivalence classes; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS COGNITIVOS E ATENCIONAIS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL